EXPLORE EMBROIDERY AND WEAVING TAPESTRY WITH SHIBORI TECHNIQUES ON OUTER READY TO WEAR CLOTHING - Fajar, Elina Almara; Falah, Asep Miftahul (CAIJ: Creative Arts Interdisciplinary Journal, 2022)
The discussion of this research is based on how to explore embroidery techniques and tapestry weaving techniques in ready-made garments with an exploration of shibori technique in the textiles to be used, so that they can provide greater value in educating fashion users to reduce the problem of textile and fashion waste pollution. This study uses an experimental method, namely a research method that explores processing and dyeing techniques for natural fibers and uses the design thinking phase, which consists of five phases, namely Empathize, Define, Ideate, Prototype, Test. The research design used a t-test as an experimental design. The data collection was done by literature study in journals, books, articles and internet. In this study, the design is limited by the use of natural fibers in the form of cotton fabric and the use of natural dyes (Secang and Jambal). The product design is limited to wearable outerwear products that have a simple design but are still in line with current trends. The results of this study are fashion prototypes using embroidery techniques and tapestry weaving with the shibori dyeing method applied to ready-to-wear outerwear using natural fibers as cotton fabric material. Keywords: Fashion, Weaving, Tapestry, Shibori Technique, Ready To Wear